2021
DOI: 10.3892/etm.2021.10002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum transforming growth factor‑β1 and procollagen type I N‑propeptide in post‑tuberculosis tracheobronchial stenosis

Abstract: Non-invasive strategies for monitoring posttuberculosis (TB) tracheobronchial stenosis (PTTS) are clinically important but currently lacking. Transforming growth factor-β1 (TGF-β1) and procollagen type I N-propeptide (PINP) have been identified as markers of fibrosis. The present study aimed to investigate the clinical significance of serum TGF-β1 and PINP in PTTS. Serum samples were collected from 119 patients with tracheobronchial TB after the condition was treated for at least 6 months (59 patients with air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Given that brosis plays an important part in the genesis and development of BAS, the inhibition of brosis can alleviate traumatic tracheal stenosis (Enyuan, et al,2018;Xiao, et al,2020;Wu, et al,2021). Fibrosis is hallmarked by the aggregation of myo broblasts, the proliferation of collagen and the deposition of extracellular matrices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that brosis plays an important part in the genesis and development of BAS, the inhibition of brosis can alleviate traumatic tracheal stenosis (Enyuan, et al,2018;Xiao, et al,2020;Wu, et al,2021). Fibrosis is hallmarked by the aggregation of myo broblasts, the proliferation of collagen and the deposition of extracellular matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the genesis and progression of BAS are caused by airway mucosal in ammation, mucosal abnormal hyperplasia, epithelial-mesenchymal transition (EMT) and brous scar formation under the in uence of various factors such as infection, trauma and hypoxia, which leads to stenosis (Shi, et al,2021;Wu, et al,2021;Wei, et al,2023). Owing to the action of cytokines like transforming growth factor-β1 (TGF-β1) following BAS, tracheobronchial broblasts aberrantly aggregate and proliferate, which results in the proliferation of granulation tissues and brosis (Wu, et al,2021;Xu, et al,2021). Given that the treatment of BAS is challenging due to a paucity of speci c drugs and treatments, taking effective measures during the early stage of tracheal injury is warranted to alleviate airway injury and the pathological repair process (Enyuan, et al,2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Pulmonary hypertension (PH), as a common complication for COPD, has been reported that "TC" genotype of TRPV1 SNP rs3744683 was a protective factor for PH in COPD patients compared with the genotype of "TT" [41,42]. SNP at + 869 site of TGF-β1 has been reported in various diseases such as hepatocellular carcinoma and tracheobronchial stenosis, but no consistent conclusion in COPD [43,44]. Here, we detected SNPs of TGF-β1 in 98 COPD patients and 90 healthy volunteers, and no differences in age, gender, BMI and smoking index was found between the COPD group and the control group in our study.…”
Section: Tgf-β1 Upregulated In Copd Patients With Pulmonary Brosismentioning
confidence: 99%
“…Previous studies have suggested that the genesis and progression of BAS are caused by airway mucosal inflammation, mucosal abnormal hyperplasia, epithelial-mesenchymal transition (EMT) and fibrous scar formation under the influence of various factors, such as infection, trauma and hypoxia, which leads to stenosis (Shi, et al 2021 ; Wu, et al 2021 ; Wei, et al 2023 ). Owing to the action of cytokines like transforming growth factor-β1 (TGF-β1) following BAS, tracheobronchial fibroblasts aberrantly aggregate and proliferate, which results in the proliferation of granulation tissues and fibrosis (Wu, et al 2021 ; Xu, et al 2021 ). Given that the treatment of BAS is challenging due to a paucity of specific drugs and treatments, it is warranted to take effective measures during the early stage of tracheal injury to alleviate airway injury and the pathological repair process (Enyuan, et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%